A Modern Computer Literacy Course from the Point of View of the New Third Age Generation - E. V. Grokhotova; D. A. Barkhatova (Открытое образование (Москва), 2021)
The purpose of the study is to identify the needs, attitude and experience of third-age people in the field of using information and communication technologies in the modern stage of informatization. The modern system of additional education for older people in the field of computer literacy is now very outdated and in need of modernization. The transformation of the needs of this category of people for new knowledge and skills is caused by the rapid pace of development of digitalization, the growth of the range of electronic services and the expansion of opportunities associated with the use of information and communication technologies. The involvement of older people in these processes and the need to adapt to a new way of life actualizes the need to study what a modern digital literacy course should be from the point of view of people of the third age, namely, it is necessary to determine their needs for computer training, the experience and resources that they have.Materials and methods. The study was conducted from 2016 to 2019 on the basis of the Municipal government institution of the city of Novosibirsk “Coordination Center “Active City” among 214 people, studying under the program “Academy of Computer Literacy”, dedicated to the basics of working with computers and the Internet, organized with the support of the social programs’ development fund named after L.I. Sidorenko.The research carried out a theoretical analysis of psychological, pedagogical and scientific literature on the research topic, questioning and polling of respondents, analysis and generalization of the data obtained. The main objectives were: a) to reveal the information and communication technology resources available to respondents at home; b) to discover the motivating factors that determine the need for training in the field of computer literacy; c) to identify the requirement for the content of the computer literacy course in modern conditions in accordance with the requirements of the respondents; d) to analyze how these requirements are manifested in different age groups: 55-60 years old, 61-70 years old, 71-80 years old and over 80 years old.Results. The results of the study show the need to develop a course, not computer, but digital literacy of a new format, with the nature of flexibility, contributing to the satisfaction of any need to eliminate the problems of information activity at any level: low, intermediate or advanced. In addition, the rapidly changing information technology necessitates the provision of training that will enable the elderly person in the future to deal with any new and unknown technology. It is very important to adapt modern retirees to the new digital reality, teach them to interact with it and understand the principles of the device.Conclusion. These studies are the basis and prove the need to revise existing computer literacy courses and develop new content and teaching methods that take into account the modern needs of third age people.